The Needs of Islamic Health-Related Quality of Life Instrument: A Review - Harmy, Mohamed Yusoff; Mahadzirah, Mohamad; Rahmah, Mohd Amin; Wan Mohd Yusof, Wan Chik (2018)
One of the best ways to evaluate persons’ health quality is through measuring their Quality of Life (QoL). The QoL concept gained rapid popularity over the last four decades in assessing health. It has been used as the sole endpoint in studies designed specifically to develop a positive physical or mental well-being of sick people. The purpose of this review is to address the needs of a new Islam-specific health-related QoL instruments for Muslim patients. A literature search was conducted using electronic databases. For the purpose of the review, QoL domains from WHOQOL SRPB instrument was referred. The identified QoL instruments were then reviewed for their domains and dimensions included in it. At present, there is no specific QoL instrument to assess health-related QoL among Muslim patients’ despite being fastest-growing religion and contribute 23% of the world population. Muslims believes that Islam is a comprehensive way of life which puts religiosity and spirituality as an essential part of life. In addition, QoL is regarded as an important aspect in health care by the World Health Organization (WHO) and spiritual well-being is one of the WHO QoL dimensions. To date, no instrument has been developed to measure QoL specifically according to Islamic perspective. Hence a specific assessment tool of health-related QoL for this growing world population is highly needed. Islam is not only a religion but it’s a way of life and QoL should be beyond the religion perspectives. Therefore, this paper will present the gap found in the review of the existing QoL instruments. Identifying this gap will enable us to develop a tool which is more sensitive to the Muslim population.